Validation of the German Emotional Contagion Scale and development of a mimicry brief version - Tobias Janelt; Tobias Altmann; Danièle Anne Gubler; Marcus Roth (PLoS ONE, 2025)
The susceptibility to emotional contagion has been psychometrically addressed by the self-reported Emotional Contagion Scale. With the present research, we validated a German adaptation of this scale and developed a mimicry brief version by selecting only the four items explicitly addressing the overt subprocess of mimicry. Across three studies (N1 = 195, N2 = 442, N3 = 180), involving various external measures of empathy, general personality domains, emotion recognition, and other constructs, the total German Emotional Contagion Scale demonstrated sound convergent and discriminant validity. A bi-factor model provided acceptable fit, suggesting the factorial validity of the total scale, which is aimed to measure a general factor, representing the susceptibility to emotional contagion. Longitudinal analyses across four measurement occasions revealed high temporal stabilities for the total scale across periods of up to 1 year as well as longitudinal measurement invariance of the factor loadings and partial invariance of the intercepts and residuals. The correlation pattern of the mimicry short version was comparable to the total Emotional Contagion Scale’s correlation pattern, the unidimensional factor structure was confirmed, and it also demonstrated high temporal stabilities and longitudinal invariance. The present research underscores the relevance of susceptibility to emotional contagion and mimicry as personality constructs and provides valid measurement tools for assessing them in future research and practical contexts (e.g., assessment in the clinical or work context).